The Analysis of Tourism Industry in Kacirebonan, West Java, Indonesia - Wachyudi, Sudiana; Dewi, Ratna Puspita; Wulandari, Tresia (International Journal of Psychosocial Rehabilitation, 2020)
Indonesia is known as a country that has diversity, both in terms of culture, ethnicity, language and also abundant natural resources. Thus, this diversity could be utilized for the development of Indonesian tourism and become the preferred destination among the tourist. Indonesia as one of the tourist destinations must improve the attractiveness of each region through the maintenance of historic objects, preserving culture and the unique environment.Each region has characteristics and potential to be developed into an attractive tourist attraction such as the culture of each tribe or region, historic buildings and natural beauty. The main attraction for visiting Indonesia is its natural wealth, arts and culture, hence, there is potential to develop on the authenticity of Indonesian region. One region that has a wealth of art and culture is the City of Cirebon. This research found that hospitality, communication network and infrastructure are the main causes of the successfulness of tourism industry in Cirebon.